Global Blue Economy : Analysis, Developments, and Challenges - Islam, Md. Nazrul, 1964-; Bartell, Steven M. (Applied ecology and environmental management, 2023)
"Blue Economy is an economic arena that depends on the benefits and values realized from the coastal and marine environment. This book explains the "Sustainable Blue Economy" as a marine-based economy that provides social and economic benefits for current and future generations. It restores, protects, and maintains the diversity, productivity, and resilience of marine ecosystems, and is based on clean technologies, renewable energy, and circular material flows. This book provides a survey of the current state of understanding, activities, and policies related to the Blue Economy as it is being pursued in different industries and countries. A comprehensive resource for anyone interested"--